Shiga toxin-producing Escherichia coli in human, cattle and foods. Strategies for detection and control - Nora Lia Padola (Frontiers Research Topics, 2014)
Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen associated with both outbreaks and sporadic cases of human disease, ranging from uncomplicated diarrhoea to haemorrhagic colitis (HC) and haemolytic uraemic syndrome (HUS). STEC affects children, elderly and immuno-compromised patients. STEC is capable of producing Shiga toxin type 1 (Stx1), type 2 (Stx2) or both, encoded by stx1 and stx2 genes, respectively. These strains are likely to produce putative accessory virulence factors such as intimin (encoded by eae), an enterohaemolysin (EhxA) and an autoagglutinating protein commonly associated with eae-negative strains (Saa), both encoded by an enterohaemorrhagic plasmid. Several studies have confirmed that cattle are the principal reservoir of STEC (O157 and non-O157:H7 serotypes) and many of these serotypes have been involved in HUS and HC outbreaks in other countries. Transmission of STEC to humans occurs through the consumption of undercooked meat, vegetables and water contaminated by faeces of carriers and by person-to-person contact. Diagnostic methods have evolved to avoid selective diagnostics, currently using molecular techniques for typing and subtyping of strains. Control is still a challenge, although there are animal vaccines directed against the serotype O157:H7.